Using feminist methodologies to explore female genital mutilation/cutting and child marriage in low- and middle-income contexts - Jones, Nicola; Pincock, Kate; Alheiwidi, Sarah (Frontiers in Research Metrics and Analytics, 2024)
This paper discusses how harmful practices such as child marriage and female genital mutilation/cutting (FGM/C) can be effectively explored through feminist methodologies that centre the lived experiences of girls and young women affected by these issues. Eliminating harmful practices, which are rooted in gender inequality and have myriad life-course consequences for those who experience them, has become a global priority in recent years. However, dominant conceptualisations of the drivers and consequences of child marriage and FGM/C often fail to adequately engage with or reflect adolescent girls' own nuanced experiences and perceptions. A feminist epistemology underlines the need for research methods that can uncover and address dynamics of power and inequality, as well as the complexities of voice and agency surrounding these practices, both of which perpetuate harmful practices and marginalise the voices of those who are most affected.The paper discusses adaptations to two key sets of methodological tools used with adolescent girls in research on FGM/C in Ethiopia, and on child marriage in Bangladesh, Ethiopia, Jordan and Lebanon as part of the Gender and Adolescence: Global Evidence (GAGE) longitudinal study. The purpose of these tools was to address and shift power inequalities, both within the research process and in girls' lives more widely. The Social Network Hexagon, Marriage Chain and Marriage Decision-Making Pairs tools were used to explore child marriage decisionmaking processes and dynamics, and outcomes for adolescent girls. A vignette-based discussion on FGM/C and child marriage, and a version of a Social Network Hexagon tool, were used to improve understanding of adolescents' social networks and the extent to which these shape their options for change.We find that context-specific adaptations to the tools, determined through ongoing reflexive dialogue with local researchers, were key to creating space for deep reflection and engagement by girls. Exploring the wider structural and social dynamics that enable and constrain girls' agency and decision-making around harmful practices was also key. It enabled insights into the complex ways in which gender-and age-based social norms are exercised within girls' socio-ecological contexts, as well as possible entry points for change.